Peningkatkan Kemampuan Interaksi Sosial Anak Melalui Cerita Mamuro Di Taman Kanak-Kanak Istiqomah Lubuk Gadang - Septi Septi; Delfi Eliza (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aims to improve the ability of children's social interaction through the story of Mamuro in kindergarten Istiqomah Lubuk Gadang, West Pasaman. This type of research is Classroom Action Research which is conducted by cyclic, namely two cycles of each cycle of three meetings conducted in the kindergarten Istiqomah Lubuk Gadang. Group B children with 15 children consisted of 8 male and 7 female. The research procedure was carried out as much as II cycles. Data collection techniques used observation and documentationtechniques.